The Spiritualization of Domestic Violence in the Digital Era: Examining the Cathartic Role of Religious Institutions in Empowering Victims - Faizah, Nur (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2023)
This study delves into the intricate intersection of domestic violence, spirituality, and the digital age, aiming to understand the evolving dynamics and the role religious institutions play in providing catharsis for victims. As technology increasingly permeates our daily lives, the digital era has brought about new dimensions to the manifestation and perception of domestic violence. This research seeks to shed light on the phenomenon of spiritualization, where religious narratives and beliefs are interwoven with domestic violence experiences, either exacerbating or alleviating the trauma. Through a comprehensive review of scholarly literature, and digital ethnography, this study explores how religious institutions engage with domestic violence victims in the digital realm. It examines the ways in which religious teachings, counselling, and support mechanisms are leveraged to address the unique challenges posed by the intersection of spirituality, technology, and intimate partner violence. The research also investigates the potential pitfalls of spiritualization, considering instances where religious doctrines may inadvertently contribute to the perpetuation of abuse or hinder victims from seeking help. By analyzing online forums, social media platforms, and religious websites, the study aims to elucidate the ways in which digital spaces either facilitate or impede the spiritualization process for domestic violence victims. Furthermore, the role of religious leaders and communities in raising awareness, providing resources, and fostering a supportive environment for victims is explored. The study aims to identify best practices employed by religious institutions in addressing domestic violence in the digital age, offering insights for policymakers, advocates, and religious leaders to collaboratively develop more effective strategies for supporting victims and preventing further harm. Ultimately, this research contributes to the ongoing discourse on domestic violence, spirituality, and technology, offering a nuanced understanding of the complexities involved. The findings hold implications for both academic scholarship and practical interventions, emphasizing the need for a multidimensional approach to empower victims and create a more compassionate and informed societal response to domestic violence in the digital era. keywords: domestic violence; digital era; Islamic law.